Gambaran Studi Kasus; Analisis Keuntungan Usaha Ternak Babi di CV Anugerah - Franky N.S Oroh; Richard E. M. F Osak; Filandre Imanuel Iroth (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2023)
Pig farm is a type of business that is mostly carried out in North Sulawesi Province because pigs have a large market potential in the North Sulawesi market because socially the majority of the population in several districts in North Sulawesi has likes to consume pork side dishes. The purpose of this study was to analyze the profitability of CV. Anugerah pig farm. This research was carried out at CV. Anugerah pig farm from August to September 2022. The research method used was a case study research method. This study uses primary data and secondary data. Primary data were obtained from direct interviews with farmers using a questionnaire. Secondary data obtained from related agencies, as well as related research results. The results of profit analysis with investment criteria using NPV, Net B/C and IRR criteria show that CV Anugerah pig farm in Kanonang III Village received a revenue of Rp. 3,076,947,000 a year with a profit of Rp.564,671,420 a year. Financial analysis shows an NPV value of Rp.976,112,575, the Net B/C value is 1.96 and the IRR value is 22.89 worthy of continuing. The results of the financial feasibility analysis of CV. Anugerah pig farm were declared feasible for development, based on the results of calculating a positive NPV value at an interest rate of 12%, a Net B/C value of greater than one and an IRR value of the prevailing interest rate (12%)